STRATEGI PENINGKATAN PEREKONOMIAN LOKAL BERBASIS USAHA GULA MERAH DI KECAMATAN MATUR KABUPATEN AGAM - Miftahul Khusna Harahap; Jon Kenedi (STKIP Subang, 2025)
The background of this study is to improve the economy of the community in Matur District, Agam Regency, which still uses traditional processing methods with buffalo power. The slow production process and limited results result in low efficiency and producer income. Although sugar cane production has increased, dependence on collectors (toke) and the inability to determine prices and increasingly high production costs worsen the economic conditions of the community. Dependence on traditional methods and low income make it difficult for producers to invest in technology that can increase efficiency. This study shows that although this sector has great potential, challenges in access to financing and production management are still major obstacles to improving the quality of life of brown sugar producers in Matur District. Brown Sugar Producers in Matur District, Agam Regency, are the subjects of qualitative research methodology. The data collection methods used are questionnaires, observations, interviews, and literature reviews. The SWOT analysis method is used in data analysis. Interviews using the IFE, EFE, and SWOT matrices, as well as analysis of the weighted score table are necessary steps in determining internal and external factors. There are four strategies to improve the regional economy in the SWOT matrix. Based on the research results, W-O obtained the highest score of 3.58, followed by S-O with a score of 3.58, S-T with a score of 2.42, and W-T with a score of 2.4. There are four tactics that can be used to improve the regional economy, namely: utilizing strengths to take advantage of market opportunities, taking advantage of market opportunities, and taking advantage of market opportunities.